Asymptomatic Cerebral Emboli Following Carotid Artery Stenting: A Diffusion-Weighted MRI Study - Erkan Köklü; Şakir Arslan; Elif Sarıönder Gencer; Nermin Bayar; Çağın Mustafa Üreyen; Zehra Erkal; Ahmet Genç; Ramazan Güven; Oğuz Kaan Kaya; Muhammet Rıdvan Ersoysal (Anatolian Journal of Cardiology, 2022)
Background: Silent cranial embolism due to carotid artery stenting has been demonstrated to cause dementia, cognitive decline, and even ischemic stroke. The purpose of this study was to compare the periprocedural asymptomatic cranial embolism rates of different stent designs used for extracranial carotid stenosis with diffusion-weighted magnetic resonance imaging.